2014
DOI: 10.1093/ndt/gfu292
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and validation of cutoffs for clinical use of cell cycle arrest biomarkers

Abstract: BackgroundAcute kidney injury (AKI) remains a deadly condition. Tissue inhibitor of metalloproteinases (TIMP)-2 and insulin-like growth factor binding protein (IGFBP)7 are two recently discovered urinary biomarkers for AKI. We now report on the development, and diagnostic accuracy of two clinical cutoffs for a test using these markers.MethodsWe derived cutoffs based on sensitivity and specificity for prediction of Kidney Disease: Improving Global Outcomes Stages 2–3 AKI within 12 h using data from a previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
183
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 235 publications
(203 citation statements)
references
References 30 publications
13
183
0
7
Order By: Relevance
“…Consequently, research in the last decade has focussed on the discovery and validation of more specific and sensitive markers of tubular damage/functional impairment. The most advanced biomarkers promise to identify patients at risk of AKI, diagnose AKI earlier than conventional tests and prognosticate risk of progression, including need for (RRT) renal replacement therapy [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The hope is that, with such an approach and more timely and relevant interventions, the outcome of patients with AKI can be improved.…”
mentioning
confidence: 99%
“…Consequently, research in the last decade has focussed on the discovery and validation of more specific and sensitive markers of tubular damage/functional impairment. The most advanced biomarkers promise to identify patients at risk of AKI, diagnose AKI earlier than conventional tests and prognosticate risk of progression, including need for (RRT) renal replacement therapy [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The hope is that, with such an approach and more timely and relevant interventions, the outcome of patients with AKI can be improved.…”
mentioning
confidence: 99%
“…The SAPPHIRE study 6,7 showed that two novel cell cycle arrest biomarkers, tissue inhibitor of metalloproteinase-2 and urinary insulin-like growth factor binding protein 7, largely outperformed existing markers. Whether these markers can predict the need for or duration of renal replacement therapy is currently under investigation.…”
Section: Cycle Cell Arrest Biomarkersmentioning
confidence: 99%
“…Many studies have shown that the product of the concentration of these proteins TIMP2·IGFBP7 in urine (Astute Medical, San Diego, CA, USA) is an early indicator of risk for AKI. [23][24][25][26][27][28] As the first available AKI biomarker test in the USA, urinary TIMP2·IGFBP7 was cleared in 2014 by the US FDA. 29 In this study, we tested the hypothesis that urinary TIMP2·IGFBP7 collected directly prior and after PBC administration can predict the development of AKI.…”
Section: Introductionmentioning
confidence: 99%